Education for Sustainable Development - Reflections Before the Announcement of the New Decade for Sustainable Development (2020-2030) - Batorczak, Anna; Klimska, Agnieszka (Studia Ecologiae et Bioethicae, 2020)
The paper is a reflection on the state of education for sustainable development (ESD) in Poland, before the announcement of the Decade for Sustainable Development 2020-2030. Its goal was to assess the implementation of ESD in our country, and to develop recommendations for its effectiveness. An analysis of the current core curriculum for primary schools, secondary schools, and technical secondary schools, showed the benefits of providing ESD. Reference was made to research carried out by experts from Stanford University and the “Water Explorer” project. The findings show that although the concept of sustainable development has been taken into account in the core curriculum, the content of environmental education is still being implemented in practice. It turns out that, in view of all the benefits and expectations, ESD is not the “heart and driving force” of the entire education system in Poland. The need for programmes enabling the acquisition of skills and competences for environmental protection, as well as actions motivating students to responsibly react to changes that occur in the environment, still prevail. ESD should be integrated into policies and strategies, developed in the curricula, and widely implemented in schools. It is also necessary to prepare, even train teachers to conduct ESD, point to effective methods, and equip them with appropriate implementation tools. It remains to be seen if the adoption of the “new Decade” will bring positive changes in the field of ESD implementation in Polish schools.